Sistem Kontrol Time Based Scheduling Menggunakan PLC Untuk Efisiensi Konsumsi Daya Listrik Pada Studio Musik. - Gita Rolland Ibanez; Ayusta Lukita Wardani; Daeng Rahmatullah; As’ad Shidqy Aziz (CV. Akira Java BUlu, 2026)
Unscheduled electricity usage in music studios may lead to energy wastage due to electrical loads remaining switched on outside operating hours. This study aims to design and implement a Time-Based Scheduling system using an Omron Programmable Logic Controller (PLC) and a Haiwell Human–Machine Interface (HMI) to automate the operation of electrical loads according to predetermined schedules. The system is equipped with a PZEM sensor to monitor electrical parameters in real time and a capacitor to compensate reactive power and improve the power factor. the research method consisted of hardware and software design, system implementation, and performance testing. System performance was evaluated by comparing electricity consumption before and after the implementation of the Time-Based Scheduling system. In addition, the accuracy of the PZEM sensor was assessed by comparing its measurements with those obtained using a clamp meter. the results demonstrate that the system successfully controlled electrical loads automatically according to the predefined schedule. The PZEM sensor produced measurements that closely matched the reference instrument, with average deviations of 2.24 V for voltage and 0.0058 A for current. Electricity consumption decreased from 55 Wh to 52 Wh, resulting in an energy saving of 5.45%. Although the reduction in energy consumption was relatively modest, the proposed system improved operational discipline, reduced the potential for human error, and supported more efficient electricity management.